History of art a survey of the major visual arts from the dawn of history to the present day - Janson, H. W. (Horst Woldemar) 1913-1982; Janson, Dora (Harry N. Abrams, Inc., Publishers, 1962)
Introduction: Artist and his public -- pt. 1. Ancient world -- ch. 1. Magic and ritual - the art of prehistoric man -- ch. 2. Egyptian art -- ch. 3. Ancient Near East -- ch. 4. Aegean art -- ch. 5. Greek art -- ch. 6. Etruscan art -- ch. 7. Roman art -- ch. 8. Early Christian and Byzantine art -- pt. 2. Middle Ages -- ch. 1. Islamic art -- ch. 2. Early Medieval art -- ch. 3. Romanesque art -- ch. 4. Gothic art -- pt. 3. Renaissance -- ch. 1. "Late Gothic" painting, sculpture, and the graphic arts -- ch. 2. Early Renaissance in Italy -- ch. 3. High Renaissance in Italy -- ch. 4. Mannerism and other trends -- ch. 5. Renaissance in the north -- ch. 6. Baroque in Italy and Germany -- ch. 7. Baroque in Flanders, Holland, and Spain -- ch. 8. Barouque in France and England -- pt. 4. Modern world -- ch. 1. Neoclassicism and Romanticism -- ch. 2. Realism and Impressionism -- ch. 3. Post-Impressionism -- ch. 4. Twentieth-century painting and sculpture -- ch. 5. Twentieth-century architecture